An Alternative Suture Technique for Fluid Leakage Around the Speech Prosthesis - Durna, Yusuf Muhammed; Hamit, Bahtiyar; Demirhan, Hasan; Yigit, Ozgur (Lippincott Williams & Wilkins, 2025)
Objectives: Speech problems after total laryngectomy have been tried to be solved by different methods over time. However, it has been reported that the most successful method is tracheoesophageal fistula opening and speech prosthesis placement. Patients using speech prosthesis may encounter problems such as swallowing the prosthesis and saliva leakage around the prosthesis. The aim of this study was to demonstrate the effectiveness of an alternative suture technique in preventing fluid leakage around the prosthesis. Methods: After ethics committee approval, 54 patients using speech prosthesis were included in this study. There were 14 patients in the study group who applied for replacement due to saliva leakage around the voice prosthesis and swallowing the voice prosthesis, and 40 patients in the control group who applied for replacement due to other reasons (leakage through the prosthesis, fungal infection around the prosthesis, obstruction of the prosthesis valve, inability to speak due to prosthesis valve problem). The time elapsed after the previous exchange of the patients in the study and control groups was recorded. Patients in the study group underwent fistula narrowing with a suture technique under local anesthesia. Afterward, the patients were followed up until the next voice prosthesis replacement. The data obtained were analyzed with SPSS 23.0. Results: In the study group, the average time for voice prosthesis replacement before constricting suture placement was 2.64 months (range: 1.5-4.5), and after suturing, it was 7.71 months (range: 5-13). In the control group, the average time for voice prosthesis replacement was 8.5 months (range: 6-17). The difference between the replacement time before and after suturing in the study group was statistically significant (P<0.0001). However, the difference between the replacement time after suturing in the study group and the replacement time in the control group was not statistically significant (P=0.279). Conclusion: The constricting suture method applied in patients with frequent prosthesis changes due to tracheoesophageal fistula enlargement is a complication-free, quick, and easy-to-apply, low-cost method that does not compromise patient comfort and significantly extends the duration of prosthesis use. It can be used in selected patients as a method that enhances patient comfort and reduces treatment costs.
Keywords: Provox; speech prosthesis; suture technique; tracheoesophageal fistula